Analisis Isi Pesan Altruisme pada Akun TikTok @mr.kingthread Batik Benang Raja - Siska Andriani Putri; Ratnaningrum ZD; Rakhmad S. Ramadhani (Pusat Riset dan Inovasi Nasional, 2025)
The development of digital technology has brought significant changes in the patterns of social interaction in society. Social media, especially TikTok, now functions not only as a means of entertainment but also as an effective medium for disseminating social, cultural, and humanitarian values. One interesting phenomenon in this context is the emergence of altruistic content, namely messages that represent caring, kindness, and selfless assistance. Content with altruistic nuances has its own appeal because it can create emotional closeness with the audience and has the potential to be used by business actors as a communication strategy to build a positive brand image. This study aims to identify and describe the forms of altruistic messages displayed in the TikTok account @mr.kingthread owned by Batik Benang Raja. The study used a descriptive qualitative approach with a content analysis method based on the altruism theory of Eisenberg and Mussen, as well as the six stages of content analysis according to Klaus Krippendorff. Data were collected from 24 videos uploaded between January 1–31, 2025, through observation and documentation techniques. Then, they were analyzed and categorized into six indicators of altruism: sharing, cooperation, helping, donating, honesty, and generosity. The results of the study show that @mr.kingthread's content consistently displays altruism through sincere, emotional, and easily accepted actions by the audience. The aspect of donating emerged as the most dominant element, followed by aspects of cooperation, helping, and sharing. The natural, authentic, and uncontrived message delivery strengthens emotional closeness with the audience and increases public trust in Batik Benang Raja's image as a brand that cares about humanitarian values. In conclusion, the altruism-based communication strategy through TikTok has proven effective in spreading humanitarian values, strengthening the company's positive image, and fostering a spirit of sharing among the audience.